Role of Institutions for the Elderly in Senile Dementia - Ojika, Kosei; Niimi, Tatsuji; Yoshida, Tatsuya; Inagaki, Toshiaki; Hashizume, Yoshio; Yamamoto, Toshiyuki; Inagaki, Aki (Nihon Rōnen Igakkai zasshi, 1994)
The purpose of this study was to assess the role of institutions for the elderly, and special nursing homes in particular, with regard to senile dementia. The subjects consisted of 81 cases who were institutionalized in our special nursing home from early November, 1992 to late October, 1993. Of these, 37 cases (45.7%) showed clinical dementia at the time of institutionalization. The severity and respective percentages of dementia were as follows: slight degree 32.4%, moderate degree 27.0% and severe degree 40.6%. The severity of dementia demonstrated significant correlation with age, Hasegawa's Dementia Scale, activity of daily living and physical conditions. The admission rate (40.5%) of the demented group for physical diseases was significantly higher than that (22.7%) of the nondemented group. The majority of families of both groups first sought advice at institutions other than our special nursing home and the welfare office in the city, prior to being institutionalized. The referral rate from such institutions was far higher than that for direct entry from their homes. We consider that special nursing homes, in addition to carrying for daily living requirements, should pay great attention to physical diseases in patients suffering from senile dementia, and cooperate with medical institutes, particularly referring hospitals, and other welfare and health facilities, in this regard.